Multicentre observational study of quality of life after surgical palliation of malignant gastric outlet obstruction for gastric cancer. Issue 6 (22nd December 2017) - Fujitani, K; Ando, M; Sakamaki, K; Terashima, M; Kawabata, R; Ito, Y; Yoshikawa, T; Kondo, M; Kodera, Y; Yoshida, K
Abstract: Background: Quality of life (QoL) is a key component in decision-making for surgical palliation, but QoL data in association with surgical palliation in advanced gastric cancer are scarce. The aim of this multicentre observational study was to examine the impact of surgical palliation on QoL in advanced gastric cancer. Methods: The study included patients with gastric outlet obstruction caused by incurable advanced primary gastric cancer who had no oral intake or liquid intake only. Patients underwent palliative distal/total gastrectomy or bypass surgery at the physician's discretion. The primary endpoint was change in QoL assessed at baseline, 14 days, 1 month and 3 months following surgical palliation by means of the EuroQoL Five Dimensions (EQ-5D™) questionnaire and the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire gastric cancer module (QLQ-STO22). Secondary endpoints were postoperative improvement in oral intake and surgical complications. Results: Some 104 patients (23 distal gastrectomy, 9 total gastrectomy, 70 gastrojejunostomy, 2 exploratory laparotomy) were enrolled from 35 institutions. The mean EQ-5D™ utility index scores remained consistent, with a baseline score of 0·74 and the change from baseline within ± 0·05. Gastric-specific symptoms showed statistically significant improvement from baseline. The majority of patients were able to eat solid food 2 weeks after surgery and tolerated it thereafter. The rate of overall morbidity of grade III or more according to the Clavien–Dindo classification was 9·6 per cent (10 patients) and the 30-day postoperative mortality rate was 1·9 per cent (2 patients). Conclusion: In patients with gastric outlet obstruction caused by advanced gastric cancer, surgical palliation maintained QoL while improving solid food intake, with acceptable morbidity for at least the first 3 months after surgery. Registration number 000023494 (UMIN Clinical Trials Registry). Graphical Abstract: A multicentre prospective observational study was conducted in patients with gastric outlet obstruction caused by advanced gastric cancer. Surgical palliation, gastrectomy or gastrojejunostomy maintained patient quality of life while improving solid food intake with acceptable surgical toxicity for at least the first 3 months after surgery. Improves gastric-specific symptoms